Investigation of the Relationship Between the Levels of Cigarette Addiction and Depression Levels of University Students - ÖZEL, Yasemin (Acibadem Universitesi Saglik Bilimleri Dergisi, 2023)
Purpose: The study was conducted to be cross-sectional in order to determine the relationship levels between smoking and depression and to define the sociodemographic characteristics that make a significant difference. Methods: The study was conducted with 280 students who agreed to participate in the study and stated that they smoke. The research data were conducted with university students who met the sampling inclusion criteria, and students with medium and high cigarette addiction levels who agreed to participate in the study. In the study, the "Psychological Addiction Assessment Test" and "BURNS Depression Scale" were used to evaluate the personal and addiction-related characteristics of cigarette addicts. Results: The participants of 66.3% are between the ages of 19 and 22 and 64.2% are women. Findings of the answers given to the questions directed to the smoking variable; 29.8% started smoking before the age of 17, 70.2% after the age of 18, 23.8% smoked for more than 4 years, 37.6% used 1 pack of cigarettes a day, 51.1% of them stated that they had never tried to quit smoking before, 33.3% of their mothers and 75.2% of them their fathers were smoking A statistically high positive correlation was obtained between the BDI total score and the SBBT scale score (p
Keywords: Psychiatry; Depression; smoking; addiction.; Psikiyatri; 4. Education; 16. Peace & justice